PRINCIPAL DIRECTIONS OF MATHEMATICAL AND ECONOMICAL MODELING OF THE RESIDENTIAL REAL ESTATE MARKET - Olga A. Sidorenko (Статистика и экономика)
The article considers the historical studies of economical and mathematical modeling of residential real estate market; also it includes the survey of the development of modern dwelling-construction business model. On the basis of the analysis of different resources of studies an econometric model for the residential real estate market is suggested and developed.